PENGEMBANGAN MEDIA PEMBELAJARAN KOTAK DAN KARTU MISTERIUS UNTUK MENINGKATKAN HASIL BELAJAR - Nasiyah, Nasiyah; Mariatun, Ika Lis; Sholeh, Yusrianto (STKIP Persada Khatulistiwa Sintang, 2023)
Education is always developing and can be seen from the various findings and the increasing components of the existing education system. The learning outcomes obtained by students are a reflection of the learning process with the learning model and learning media used. The purpose of this study was to develop learning media for mysterious boxes and cards in the Economics subject of Class XI at Nurusshaleh High School. The type of research used is Research and Development using procedures developed by Brog and Gall. The steps used are: Analysis and potential problems, Data Collection, Product Design, Design Validation, Design Revision, Product Testing. The Material and Media testing phase is carried out by media experts. The data in this study are in the form of qualitative and quantitative data. The research instrument was a questionnaire on student learning motivation and a questionnaire on the assessment of mysterious boxes and cards by experts. Based on the development obtained an average of the validation of material experts 29,5, media experts 9,625, learning practitioners 10,265 and student responses with an average of 11,625, learning outcomes obtained from an average pretest score of 52,5 an average posttest score of 76,1. Based on the results of the research that has been done, it means that the mysterious box and card media are in the good category and are suitable for use in class XI SMA Nurusshaleh.